How Students Seek Information When Studying at Home? A Case Study in Pekalongan High Schools - Ummi Laila Salamah ,; Ganggi, Roro Isyawati Permata (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
The Covid-19 has hampered students’ activities to visit the library. Thus, it changes students’ behavior in accessing information once studying at home. This paper studied the information seeking behavior of high school students in Pekalongan during the pandemic. This study used descriptive quantitative methods that collect research data using online questionnaires to research respondents. The research sample used the simple random sampling technique. The data was then analyzed by using descriptive statistical analysis of SPSS version 26th edition. The results showed that the information seeking behavior of high school students in Pekalongan during school from home occurs due to the Context of Information Needs (2, 88); Activating Mechanism (2.69) and risk/reward (3.07); Intervening variables in Psychological (3.08), Role-related or Interpersonal (3.37), Environmental (2.98), and Source Characteristics (2.68). Additionally, indicating the level of information seeking, Passive Search (3.07), Active Search (2.79), Ongoing Search (3.04), and Information processing and use (2.74).